Garlic (Allium sativum) Stimulates Lipopolysaccharide‐induced Tumor Necrosis Factor‐alpha Production from J774A.1 Murine Macrophages. (4th November 2014) - Sung, Jessica; Harfouche, Youssef; De La Cruz, Melissa; Zamora, Martha P.; Liu, Yan; Rego, James A.; Buckley, Nancy E.
<x xml:space="preserve">Abstract</x> Garlic (Allium sativum) is known to have many beneficial attributes such as antimicrobial, antiatherosclerotic, antitumorigenetic, and immunomodulatory properties. In the present study, we investigated the effects of an aqueous garlic extract on macrophage cytokine production by challenging the macrophage J774A.1 cell line with the garlic extract in the absence or presence of lipopolysaccharide (LPS) under different conditions. The effect of allicin, the major component of crushed garlic, was also investigated. Using enzyme‐linked immunosorbent assay and reverse transcriptase‐quantitative polymerase chain reaction, it was found that garlic and synthetic allicin greatly stimulated tumor necrosis factor‐alpha (TNF‐α) production in macrophages treated with LPS. The TNF‐α secretion levels peaked earlier and were sustained for a longer time in cells treated with garlic and LPS compared with cells treated with LPS alone. Garlic acted in a time‐dependent manner. We suggest that garlic, at least partially via its allicin component, acts downstream from LPS to stimulate macrophage TNF‐α secretion. © 2014 The Authors. Phytotherapy Research published by John Wiley & Sons, Ltd.